SPURIOUS RESPONSE SUPPRESSION IN THREE POLES HAIRPIN BANDPASS FILTER USING DEFECTED GROUND STRUCTURES - Touhami, N. Amar; Zakriti, A.; Lamsalli, M.; Boussouis, M.; Tribak, A. (European Scientific Journal, ESJ, 2013)
The demand of high data rate in wireless communications requires higher system bandwidth. In this work, the design of wideband BPF with suppression of higher harmonics has brought about by considering the UWB BPF as a hairpin filter structure with DGS BSF. As a result, the structure is simple and compact. The expected result of a simple BPF together with DGS is to have a compact UWB bandpass filter with significantly higher harmonics suppression. The filter performances are exhibits |S21| more than -0.2 dB, |S11| less than -10dB, center frequency of proposed filter is around 4GHz with operating bandwidth 38% and can suppress unwanted passband to below -25 dB